Just Another Meeting?: Investigating Mentoring for Early Childhood Teachers in Victoria. Issue 2 (May 2015) - Morrissey, Anne-Marie; Nolan, Andrea
IN A TIME OF REFORM FOR children's services in Australia, this paper explores the current mentoring programs on offer to the early childhood sector in the state of Victoria. The commissioned research involved the mapping of existing mentoring programs, supported by an extensive literature review. A thematic analysis of the data identified the following aspects as impacting on the success of the programs: the value placed on mentoring; the mentor's role; the level of support and training for mentors; the availability of resources; the divisions between mentoring and other management functions; tailoring of mentoring to individual professional desires and needs; and the presence or absence of formal evaluations to inform the future success of programs. The questions raised by this research prompt further consideration as to what mentoring for early childhood practitioners should look like in the future, especially related to collaborative practice and the balance between autonomy and guidance.